Democracy, populism and neoliberalism in Ukraine on the fringes of the virtual and the real - Bajša, Olʹga Anatolʹevna ca. 20./21. Jh (Routledge, 2022)
"This book explores the reasons behind the unexpected rise to power of Ukraine's President Volodymyr Zelensky, a former reality TV star with no political background, and offers an in-depth analysis of the populist messages he delivered to the Ukrainian people via his TV show. Taking a discourse analysis approach, the author draws on two main arguments of critical scholarship: the "populist explosion" of the recent decade came as a reaction to the inequalities and injustices of the global neoliberal order, and the success of neoliberalism can be explained by its ability to mask itself under attractive progressive covers. Developing these lines of argument, the book demonstrates not only how the "populist explosion" can lead to further neoliberalization, but also that the euphemizing effect can be achieved by mixing the virtual and the real, as in the case of Zelensky. This first of its kind study will resonate with any scholar or upper-level student working on populism, neoliberalism, political communication, media studies, political science, European studies, Ukrainian studies, and discourse analysis"--...
Keywords: Zelensʹkyj, Volodymyr Oleksandrovyč -- 1978-; Geschichte 2015-2020; Populismus; Politik; Neoliberalismus; Fernsehserie